2006
DOI: 10.1111/j.1365-2699.2006.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical biogeographical patterns of the species of Bursera (Burseraceae) and their taxonomic implications

Abstract: Aim The plant genus Bursera, with 104 species of trees and shrubs, has been used as a model for biogeographical analyses because of its high species richness and large number of endemic species. The biogeographical patterns of Bursera and their implications for its phylogenetic classification are reviewed in order that some hypotheses on the historical biogeography of tropical Mexico can be proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 42 publications
3
50
0
16
Order By: Relevance
“…2B): three in the Transmexican Volcanic Belt, one in the southern Sierra Madre Oriental, one in the eastern Sierra Madre del Sur, one in the highlands of Chiapas, and three in the boundaries between two provinces. They concluded that taxa isolated in the highlands of Chiapas (as well as Guatemala) at the end of the Pleistocene may represent the southernmost Nearctic relicts in Mesoamerica, and that the other biogeographic provinces, together with the Sierra Several other studies have contributed to the recognition of similar generalized tracks and nodes, and to the identification of smaller generalized tracks (Luna-Vega et al 1999, 2000, 2001, Morrone et al 1999, Morrone and Escalante 2002, Escalante et al 2003, Márquez and Morrone 2003, Ochoa et al 2003, Morrone and Gutiérrez 2005, Espinosa et al 2006, Contreras-Medina et al 2007a, Mariño-Pérez et al 2007, Toledo et al 2007, García-Marmolejo et al 2008). …”
Section: Identification Of Biotic Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B): three in the Transmexican Volcanic Belt, one in the southern Sierra Madre Oriental, one in the eastern Sierra Madre del Sur, one in the highlands of Chiapas, and three in the boundaries between two provinces. They concluded that taxa isolated in the highlands of Chiapas (as well as Guatemala) at the end of the Pleistocene may represent the southernmost Nearctic relicts in Mesoamerica, and that the other biogeographic provinces, together with the Sierra Several other studies have contributed to the recognition of similar generalized tracks and nodes, and to the identification of smaller generalized tracks (Luna-Vega et al 1999, 2000, 2001, Morrone et al 1999, Morrone and Escalante 2002, Escalante et al 2003, Márquez and Morrone 2003, Ochoa et al 2003, Morrone and Gutiérrez 2005, Espinosa et al 2006, Contreras-Medina et al 2007a, Mariño-Pérez et al 2007, Toledo et al 2007, García-Marmolejo et al 2008). …”
Section: Identification Of Biotic Componentsmentioning
confidence: 99%
“…Some authors have provided cladistic biogeographic analyses of Mexico (Liebherr 1991, 1994, Marshall and Liebherr 2000, Flores Villela and Goyenechea 2001, Espinosa et al 2006, Contreras-Medina et al 2007b. Escalante et al (2007) analyzed 40 plant and animal taxa distributed in Mexico and extending to both the Nearctic and Neotropical regions.…”
Section: Testing Relationships Among Biotic Componentsmentioning
confidence: 99%
“…They implemented a program (TASS) that identifies paralogy-free subtrees from each taxon-area cladogram analysed (Nelson & Ladiges, 1995;Ladiges & al., 1997Ladiges & al., , 2005. (Marshall & Liebherr, 2000;Flores-Villela & Goyenechea, 2001;Espinosa & al., 2006), and parsimony analysis of endemicity (Morrone & al., 1999;Espinosa & al, 2000;Luna & al., 2001;D?vila-Aranda & al, 2002;Morrone & Escalante, 2002;Aguilar-Aguilar & al., 2003). (Marshall & Liebherr, 2000;Flores-Villela & Goyenechea, 2001;Espinosa & al., 2006), and parsimony analysis of endemicity (Morrone & al., 1999;Espinosa & al, 2000;Luna & al., 2001;D?vila-Aranda & al, 2002;Morrone & Escalante, 2002;Aguilar-Aguilar & al., 2003).…”
mentioning
confidence: 99%
“…The regionalization of Rzedowski (1978) is available in digital format, enabling the distributional data to be analysed with a Geographic Information System (GIS). We extended some Mexican areas of endemism to adjacent areas of Central America (following Morrone, 2001Morrone, , 2006 and North America (following Takhtajan, 1986), in order to include all the present-day natural dis tributions of gymnosperms from the Mexican Transition Zone. & al., 1983;Stevenson & al., 1986;McVaugh, 1992;Mo retti & al., 1993;Thieret, 1993;Farjon & Styles, 1997;Medina & D?vila-Aranda, 1997;Narave & Taylor, 1997;Vovides, 1999;Contreras-Medina & al., 2001,2003.…”
mentioning
confidence: 99%
“…The units used in PAE are predetermined areas of any kind, such as arbitrary operational units (van Soest, 1994), quadrats (Morrone 1994a, Linder 2001a,b, García-Barros et al 2002, Morrone and Escalante 2002, Rovito et al 2004, García-Barros, 2003, Rojas-Soto et al 2003, Vergara et al 2006, Herrera-Paniagua et al 2008, Meng et al 2008, Löwenberg-Neto and de Carvalho, 2009, Ramírez-Barahona et al 2009), islands (Bisconti et al 2001, Trejo-Torres and Ackerman 2001, Fattorini 2002, localities (Raxworthy and Nussbaum, 1996, Ron 2000, Anstey et al 2003, Ribichich, 2005, Ramírez-Arriaga and Martínez-Hernández, 2007, Gates et al 2010, Aguirre et al 2011, interfluvial regions (Silva and Oren 1996), hydrological basins (Aguilar-Aguilar et al 2003, Huidobro et al 2006, politically defined areas (Cué-Bär et al 2006, Nelson 2008, Ribeiro and Eterovic 2011, biogeographical areas (Glasby andAlvarez 1999, Vega et al 1999), predefined areas of endemism (Goldani et al 2002, Katinas et al 2004, Espinosa et al 2006, Albert and Carvalho 2011. In a few analyses, latitudinal (Morrone et al 1997…”
Section: Fattorini 2017mentioning
confidence: 99%